DAMPAK PENGHINDARAN PAJAK, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Krisyanti, Oktafiaya; Syahzuni, Barlia Annis (Jurnal Riset Akuntansi Politala, 2025)
Research to examine the implications of independent variables, including tax avoidance, entity size, and profitability on firm value as a dependent variable. The focus of the research data is on food and beverage sub-sector entities on the Indonesia Stock Exchange for the 2020-2023 period. The research population includes 94 entities, with the number of samples that meet the research criteria of 30 entities or 120 data. The proxies used in the research variables are tax avoidance using the ETR-CETR proxy, entity size using the Ln total assets proxy, profitability using the ROE proxy and firm value using the modified Tobin's Q proxy. The results of data processing produce findings that tax avoidance and entity size have a significant negative impact on firm value. While profitability has a significant positive impact. The coefficient of determination (R2) value is 37.6, which means that the variables tax avoidance, entity size and profitability have an impact on firm value of 37.6% and the remaining 62.4% is influenced by other independent variables.